(untitled) (Quinto Sol, 2012)
This paper compares information concerning Guardia de Luján’s population and land occupation with specific economic data about the Direct Contribution tax during the first half of the 19th century in order to study the 1840s. The main goal is to show the social dynamism of this society. Although this issue was previously noticed and then developed, new data from the local history is provided since it allows us to see the socialprocess in detail (in particular, a characteristic feature that is upward and downward social mobility) not only in the long term but also in the short term. In this way, this article contributes to the study of the economic growth and the distribution of wealth and, at the same time, distinguishes the social members involved and the evolution of their fortunes.